2016
DOI: 10.1021/acschemneuro.6b00009
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Shapes the Dialogue between Environment, Microglia, and Adult Neurogenesis

Abstract: Lifestyle modulates brain function. Diet, stress levels, and physical exercise among other factors influence the "brain cognitive reserve", that is, the capacity of the brain to maintain a normal function when confronting neurodegenerative diseases, injury, and/or aging. This cognitive reserve relays on several cellular and molecular elements that contribute to brain plasticity allowing adaptive responses to cognitive demands, and one of its key components is the hippocampal neurogenic reserve. Hippocampal neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 171 publications
(364 reference statements)
1
59
0
1
Order By: Relevance
“…In addition, phagocytosis of newborn cells has also been recently shown to play a role in sculpting sex differences in the developing amygdala (VanRyzin et al, 2019). While previous work has suggested a largely detrimental effect of microglia on hippocampal neurogenesis (Valero et al, 2016), our data are in agreement with recent evidences supporting the essential role of macrophages and other immune cells in remodeling stem cells niches (Naik et al, 2018).…”
Section: Phagocytosis Reprograms Microgliasupporting
confidence: 92%
“…In addition, phagocytosis of newborn cells has also been recently shown to play a role in sculpting sex differences in the developing amygdala (VanRyzin et al, 2019). While previous work has suggested a largely detrimental effect of microglia on hippocampal neurogenesis (Valero et al, 2016), our data are in agreement with recent evidences supporting the essential role of macrophages and other immune cells in remodeling stem cells niches (Naik et al, 2018).…”
Section: Phagocytosis Reprograms Microgliasupporting
confidence: 92%
“…Interestingly, apart from their effect on developmental neurogenesis, microglia can influence adult hippocampal neurogenesis by phagocytosis of apoptotic cells (Sierra et al, 2010) and are also able to provide trophic support to new adult born neurons in the hippocampus and SVZ (for review see Gemma and Bachstetter, 2013; Ribeiro Xavier et al, 2015). It is thus likely that the mechanisms microglia use to affect developmental neuro- and astrogenesis, can also be used to influence SVZ and hippocampal neurogenesis in the adult (Aarum et al, 2003; Kanski et al, 2014; Valero et al, 2016). …”
Section: The Crosstalk Between Microglia Neural Progenitors and Astrmentioning
confidence: 99%
“…It is believed that the binding of soluble CX3CL1 to its receptor CX3CR1 maintains the "synapse pruning" function of microglia [43]. A previous study found that the number of microglia and dendritic spine density increased in CX3CR1-knockout mice at the age of 2-3 weeks.…”
Section: Discussionmentioning
confidence: 98%